Mapping 123 million neonatal, infant and child deaths between 2000 and 2017 (2019)
Objective: The aim of the descriptive, cross sectional, questionnaire-based study reported here was to explore the causes of low productivity in non-communicable diseases research among postgraduate scholars and early career researchers in Nigeria and identify measures that could facilitate increased research output. Results: The 89 respondents were masters-level, doctoral scholars and resident doctors who attended a workshop. Majorities of the respondents (over 70%) either agreed or strongly agreed that factors contributing to poor non-communicable diseases research productivity include a dearth of in-country researchers with specialized skills, inability of Nigerian researchers to work in multidisciplinary teams, poor funding for health research, sub-optimal infrastructural facilities, and limited use of research findings by policy makers. Almost all the respondents (over 90%) agreed that potential strategies to facilitate non-communicable diseases research output would include increased funding for research, institutionalization of a sustainable, structured capacity building program for early career researchers, establishment of Regional Centers for Research Excellence, and increased use of research evidence to guide government policy actions and programs.